Biomedical applications of capillary electrophoresis - Deyl, Z; Tagliaro, F; Miksík, I (Journal of chromatography. B, Biomedical applications, 1994)
After having grown through the stages of technique development and instrumentation availability, capillary electrophoresis has reached the stage of applications. This review attempts to show the potential of this technique for biomedical analysis. Rather than going into a detailed description of the technical details of the separation conditions suitable for the separation of a particular category of compounds, the focus is on the general principles and areas in which this technique can be applied and the prospects for the future. Particular emphasis is placed on the separation of complex matrices and their simplification, a daily task in biomedical laboratories. In addition, methods for the optimization of separation conditions are considered. Considerable prospects for capillary electrophoresis lie in profiling. The applicability of the technique in peptide and protein mapping is discussed in some detail. Finally, three other topics are dealt with, namely enzymic activity microassays, drug-protein binding assays and monitoring of drugs in body fluids.
Keywords: Chemistry, Clinical; Electrophoresis; klinická chemie; elektroforéza; lidé; Animals; Humans; zvířata